next | previous | forward | backward | up | top | index | toc | Macaulay2 website
Macaulay2Doc :: MonomialIdeal - MonomialIdeal

MonomialIdeal - MonomialIdeal -- monomial ideal difference

Synopsis

Description

i1 : R = QQ[a..d];
i2 : I = monomialIdeal(a^3,b^2,a*b*c)

                     3   2
o2 = monomialIdeal (a , b , a*b*c)

o2 : MonomialIdeal of R
i3 : J = monomialIdeal(a^2,b^3,a*b*c)

                     2   3
o3 = monomialIdeal (a , b , a*b*c)

o3 : MonomialIdeal of R
i4 : I - J

                    2
o4 = monomialIdeal b

o4 : MonomialIdeal of R
i5 : J - I

                    2
o5 = monomialIdeal a

o5 : MonomialIdeal of R
i6 : I - (I-J)

                     3
o6 = monomialIdeal (a , a*b*c)

o6 : MonomialIdeal of R

See also